Viral Replication and Production (IntechOpen, 2026)
Viral replication and production are always phenomenal in a virus's life cycle (either lysogenic or lytic) to produce mutated viral genomes, viral variants, and infectious viral particles. The viral infectivity of a host cell and the progression of an acute viral infection to a chronic form also rely on the pace and fidelity of viral polymerase enzymes. The intricate interplay between the viral genome and the host proteome, virus kinetics/dynamics, and the regulation of viral replication by host cellular networks and cell signaling also predicts the adaptability, evolution, and pathogenesis of highly infectious viruses. The latest advancements in biotechnology and genetic engineering have revolutionized diagnostic and treatment strategies for various viral infections, including hepatitis B and C, influenza, and COVID-19. Similarly, the design and development of various innovative artificial intelligence (AI) tools and machine learning (ML) algorithms have paved the way for elucidating viral replication, transcription, and host invasion mechanisms in great detail. This book provides an overview of the current insights into viral replication mechanisms and viral progeny processes, focusing on dengue virus (DENV), hepatitis B virus (HBV), hepatitis C virus (HCV), morbillivirus, and SARS-CoV-2. The book also briefly sheds light on the replication and biogenesis of infectious viral particles, as well as the regulation by host cell enzymes, growth factors, proteins, receptors, and cell signaling. Viral Replication and Production also concisely explicit the uses of novel gene-level approaches to treat the next generation of viral infections, and also demonstrates how AI, computational virology, ML, and mathematical modeling of viral replication, and virion dynamics could be helpful in the future prediction of an epidemic or pandemic of emerging and re-emerging viral pathogens and to evaluate their impacts on communities and healthcare systems. This book will serve as a valuable resource for further exploring viral replication mechanisms and the processes of virion biogenesis.